Respuestas

2013-09-18T03:22:54+02:00
A)  2/7+3/4= [(2*4)+(7*3)]/ 4*7 = [8+21]/28 = 29/28

b)  5/3-1/2= [(5*2)-(3*1)]/2*3 = [10-3]/6 = 7/6

c)  3/4+1/2-1/8-->   m.c.m de 4 , 2 , 8 =  [8]
                     --> [(6)+(4)-(1)]/8 =  9/8

d)  9/4-1/2+1/3 -->   m.c.m. de 4 , 2 , 3 = [12]
                        -->  [(27)-(6)+(4)]/12 = 25/12

e)  5/6+1/9--> m.c.m. de 6 , 9= [18]  --> [(15)+(2)]/ 18 = 17/18

f)   4/12+2/12-1/12 = [4+2-1]/12 = 5/12

g)  1/3+2/3-1/4-->  m.c.m de 3 , 3 , 4 = [12]
                      -->  [(4)+(8)-(3)]/12 = 9/12

h)  2/5+1/6-1/3 -->  m.c.m de 5 , 6 , 3 = [30]
                      --> [(12)+(5)-(10)]/30 = 7/30